Multi-Sensor Based on Internet of Thing (IoT) in Determining the Accuracy of Sensors for Air Temperature, Air Humidity, and Light Intensity - Muhammad Yunus; Susilo Yudoyono; Dewa Gede Eka Setiawan; Siti Fatimah; Asmiati Amir (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2026)
Multi-sensor technology based on the Internet of Things (IoT) is implemented in determining the accuracy of sensors for airtemperature, air humidity, and light intensity. The multi-sensor based on IoT consists of a DHT11 sensor to detect air temperature and humidity, and a BH1750 sensor to detect light intensity was implemented using the NodeMCU ESP8266 microcontroller, monitored via the IoT on the Blynk application on the smartphone. Data Sensor validation by comparing data from the Indonesian National Standards measuring instrument to determine the sensor accuracy. The results of testing the sensors for air temperature, air humidity, and light intensity produced average accuracies of 99.440%, 100%, and 99.874%, respectively. All sensor errors remain within the specified tolerance limit of <5%. The low error sensor results in a high accuracy value. These sensors are suitable for various monitoring needs, both in automation systems and environmental research.